Bundling Public and Charitable Supports to Cope with the Effects of the Great Recession*. (10th November 2015) - Allard, Scott W.; Wathen, Maria V.; Danziger, Sandra K.
Abstract : Objective: We examine how low‐income households have drawn upon public and charitable nonprofit sources of social assistance during and after the Great Recession. Methods: Using panel survey data collected in the Detroit Metropolitan Area in 2008 and 2010, we explore the relationships between household characteristics, program use, and bundling of assistance. Results: Roughly two‐thirds of Detroit households within 300 percent of poverty received a public safety net benefit in the previous year; about 40 percent received assistance from more than one public program. More than one in six households received help from a nonprofit charity. Low educational attainment, unemployment, and health limitations are positively related to receipt of multiple public assistance programs. Conclusions: Our findings point to persistent needs among poor and near‐poor households after the Great Recession, as well as to the reality that many low‐income households draw upon multiple sources of public assistance even when working. Many low‐income households remain detached from public and charitable sources of support even as the safety net has expanded in response to the downturn.